Transmembrane adaptor proteins in membrane microdomains: important regulators of immunoreceptor signaling - Horejsí, Václav (Immunology letters, 2004)
Membrane microdomains enriched in glycosphingolipids, cholesterol, glycosylphosphatidylinositol-anchored proteins and Src-family kinases (lipid rafts, GEMs) appear to play many important roles, especially in immunoreceptor signaling. Most transmembrane proteins are excluded from these specialized areas of membranes, notable exceptions being several palmitoylated proteins such as the T cell coreceptors CD4 and CD8, and several recently described transmembrane adaptor proteins, LAT, non-T cell activation linker (NTAL)/linker for activation of B cells (LAB), phosphoprotein associated with GEMs (PAG)/Csk-binding protein (Cbp) and LIME. All these molecules possess a very short N-terminal extracellular peptide (4-17 amino acids), transmembrane segment followed by a palmitoylation motif (CxxC) and cytoplasmic domain containing up to 10 tyrosine residues potentially phosphorylated by the Src- or Syk-family kinases. Tyrosine-phosphorylated transmembrane adaptors bind (directly via SH2 domains or indirectly) other signaling molecules such as several cytoplasmic adaptors and enzymes. LAT is indispensable for TCR signaling (and participates also at signal transduction initiated by some other receptors), NTAL/LAB appears to play a LAT-like role in signaling initiated by BCR and some Fc-receptors; PAG/Cbp cooperates with Csk, the cytoplasmic tyrosine kinase negatively regulating Src-family kinases. Additional transmembrane adaptors exist (TRIM, SIT, LAX) that are however not palmitoylated and therefore excluded from the lipid rafts; structurally and functionally, the zeta-chain family proteins tightly associated with immunoreceptors and activating NK-receptors may be also considered as transmembrane adaptors.
Keywords: Animals; mezibuněčné signální peptidy a proteiny; Rats; fosfoproteiny; Adaptor Proteins, Vesicular Transport; Adaptor Proteins, Signal Transducing; Intercellular Signaling Peptides and Proteins; adaptorové proteiny signální transdukční; lidé; Phosphoproteins; Mice; Receptors, Immunologic; membránové mikrodomény; membránové proteiny; signální transdukce; myši; Signal Transduction; receptory imunologické; krysa rodu Rattus; Membrane Proteins; Membrane Microdomains; zvířata; adaptorové proteiny vezikulární transportní; Humans